The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000348526
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of the Reverse Mode of Na<sup>+</sup>/Ca<sup>2+</sup> Exchanger Attenuates Contrast-Induced Cell Injury

Abstract: Background: The precise mechanisms underlying radiocontrast nephropathy (RCN) are not well understood. Intracellular Ca2+ overload is considered to be a key factor in RCN. The Na+/Ca2+ exchanger (NCX) system is one of the main pathways of intracellular Ca2+ overload. We investigated whether intracellular Ca2+ overload via the NCX system was involved in contrast-induced renal tubular cytotoxicity. Methods: NRK-52E cells were exposed to ioversol (100 mg iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…Further, the shape of the Ca 2+ signal in most cells mimicked a high amplitude peak plateau, which is a characteristic pathological signal that precedes acinar cell injury and pancreatitis 25, 26, 4853 and which would favor calcineurin activation 54 . A recent report demonstrated that a long incubation (of 4 hr) with ioversol, a RC that is similar to the iohexol and iopamidol we used, caused a slow, globalized increase in baseline cytosolic Ca 2+ levels in the NRK-52E renal cell line 55 . It was suggested that the RC triggered voltage-gated Ca 2+ channels or caused reversal of the plasma membrane Na + /Ca 2+ exchanger (NCX), so as to favor Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 81%
“…Further, the shape of the Ca 2+ signal in most cells mimicked a high amplitude peak plateau, which is a characteristic pathological signal that precedes acinar cell injury and pancreatitis 25, 26, 4853 and which would favor calcineurin activation 54 . A recent report demonstrated that a long incubation (of 4 hr) with ioversol, a RC that is similar to the iohexol and iopamidol we used, caused a slow, globalized increase in baseline cytosolic Ca 2+ levels in the NRK-52E renal cell line 55 . It was suggested that the RC triggered voltage-gated Ca 2+ channels or caused reversal of the plasma membrane Na + /Ca 2+ exchanger (NCX), so as to favor Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 81%
“…It has been proven that the ER stress-induced apoptosis can be mediated by ROS [22] and that oxidative stress plays an important role in the pathogenesis of CI-AKI [12,23]. In the present study, the role of ROS in the ER stress-induced apoptosis in iopromide-treated NRK-52E cells was investigated.…”
Section: Discussionmentioning
confidence: 89%
“…Cells were subcultured when the cell monolayer reached 80% confluence. Cells were exposed to increasing concentration [50, 100, 150 mg iodine (I)/ml] of iopromide for 4 h based on our previous experiment [12]. In a separate experiment, cells were divided into four groups: (A) control (cells without any treatment); (B) cells exposed to NAC (10 mmol/l); (C) cells exposed to iopromide (100 mg I/ml, 4 h), and (D) NAC (10 mmol/l) added 1 h before iopromide treatment (100 mg I/ml, 4 h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that the increased intracellular Na + concentration leads to an increased intracellular Ca 2+ which consequently affects the apoptotic process. Increased intracellular Ca 2+ has been suggested to trigger apoptosis in different cell types [40], [41]. Normally intracellular Ca 2+ is pumped out through a Na + /Ca 2+ exchanger (NCX exchangers) [42].…”
Section: Discussionmentioning
confidence: 99%